2007
DOI: 10.1007/s11769-007-0376-3
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of aluminum and fluoride in tea plant and soil of tea garden in Central and Southwest China

Abstract: The distribution of Al and F contents and the relationship between Al and F in tea plants and soils of 12 tea gardens in Central and Southwest China were investigated from October 31 to November 14, 2006. The results show that there were differences in pH, CEC, the contents of organic matter (OM), Al and F in the different soils of the tea gardens. The Al content ranged from 1196 to 7976mg/kg for old leaf, 370 to 2681mg/kg for young leaf and 285 to 525mg/kg for stem, whereas the content of F ranged from 221 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 23 publications
0
15
1
Order By: Relevance
“…The leaching rate from four leaves and a bud green tea was significantly lower than that from three leaves and a bud green tea. This might be due to that the F content in tea also increased with leaf age, and Al formed more complexes with F in old leave [5,21], thus decreasing the leaching rate. The leaching of Al from black tea and oolong tea also showed a similar trend to that of green tea with the increase of leaf age.…”
Section: Leaching Of Al From Teamentioning
confidence: 99%
“…The leaching rate from four leaves and a bud green tea was significantly lower than that from three leaves and a bud green tea. This might be due to that the F content in tea also increased with leaf age, and Al formed more complexes with F in old leave [5,21], thus decreasing the leaching rate. The leaching of Al from black tea and oolong tea also showed a similar trend to that of green tea with the increase of leaf age.…”
Section: Leaching Of Al From Teamentioning
confidence: 99%
“…Previous studies showed that the concentrations of F in tea plants are significantly different from variety to variety, even for those living in the same natural environment [17–19]. Because of the long-term allogamy, tea plants might have a wide range of genetic backgrounds that affect the absorption and accumulation of F [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…In soils, chemical sequential extraction has been employed to separate total fluoride (T‐F) presumably into water extractable fluoride (F (H2O) ), magnesium chloride (MgCl 2 ) extractable fluoride (F (MgCl2) ), fluoride bound to Mn/Fe hydroxides (F (oxides) ), fluoride bound to organic matter (F (OM) ), and residual fluoride (F (Res) ) (Fig. 2), 21–23 external fluoride can be transformed into other forms in soil solutions 24 . Another evaluation of soil fluoride is extracted independently by water (F (H2O) ) or calcium chloride (CaCl 2 ) solution (F (CaCl2) ) 22 .…”
Section: Fluoride In Soil and Bioavailability To Tea Plantsmentioning
confidence: 99%